Worldwide comparative efficacy of nutraceuticals on lipid profile. an updated systematic review and network meta-analysis. (3rd October 2022) - Osadnik, T; Golawski, M; Lewandowski, P; Morze, J; Osadnik, K; Pawlas, N; Lejawa, M; Jakubiak, G; Mazur, A; Schwingshackl, L; Gasior, M; Banach, M
Abstract: Introduction: In case of patients without indications to statin therapy, those being close to the target and especially with statin intolerance, nutraceuticals might be an additional option of hypercholesterolemia therapy. Despite a large number of nutraceuticals, little is known on their comparative efficacy due to the paucity of head-to-head comparisons. We aimed to assess the lipid-lowering effect of various nutraceuticals by means of network meta-analysis. Methods: PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials were carefully searched to identify eligible studies to the meta-analysis. We included parallel or crossover randomized clinical trials (RCT), comparing head-to-head or to placebo/no intervention, the following nutraceuticals: a) artichoke, b) berberine, c) bergamot, d) garlic, e) green tea extract, f) plant sterols and stanols, g) policosanols, h) red yeast rice (RYR), i) silymarin, j) spirulina. We did not include soy protein, fiber, and lupin trials, as unlike other nutraceuticals they are in fact dietary interventions. Due to strikingly inconsistent results of policosanols RCTs carried out in Cuba and other countries, we excluded Cuban trials from main analysis. Results: From the initially identified 4151 articles we finally included 131 studies. As some studies reported clinically different groups separately, they were split and finally we included 136 records, 134 with data on total cholesterol (TC), 125 with data on low-density cholesterol (LDL-C), 127 that provided information on high-density cholesterol (HDL-c) and 129 that included data regarding triglycerides (TG). Pooled studies covered data for 6755 patients randomized to nutraceutical arms and 6370 randomized to receive placebo/no intervention. For reducing TC bergamot, was identified as the most effective approach (P-score = 1.0) followed by RYR (0.90) and berberine (0.76). For increasing HDL-C, bergamot (0.98), berberine (0.85), and RYR (0.77) were the most effective. While evaluating LDL-C reduction, bergamot (1.00) and RYR (0.90) showed the highest reduction efficacy. Reducing effect of investigated nutraceuticals on TG levels was the highest for bergamot (1.00) and RYR (0.78). Majority of reports regarding Cuban policosanol trials implicated very high effectiveness of those nutraceuticals, which was in contrast to trials conducted in other countries Conclusions: Bergamot, berberine, and RYR seemed to be most effective nutraceuticals in terms of lipid-lowering efficacy. Alleged high effectiveness of policosanols was not confirmed in our analysis. This analysis might support the physicians and patients' decisions to use only those nutraceuticals of confirmed efficacy. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Medical University of Silesia, Katowice